NMR and crystallographic structures of the FK506 binding domain of human malarial parasite Plasmodium vivax FKBP35 - Alag, Reema (2012)
The emergence of drug-resistant malaria parasites is the major threat to effective malaria control, prompting a search for novel compounds with mechanisms of action that are different from the traditionally used drugs. The immunosuppressive drug FK506 shows an antimalarial activity. The mechanism of the drug action involves the molecular interaction with the parasite target proteins PfFKBP35 and PvFKBP35, which are novel FK506 binding protein family (FKBP) members from Plasmodium falciparum and Plasmodium vivax, respectively. Currently, molecular mechanisms of the FKBP family proteins in the parasites still remain elusive. To understand their functions, here we have determined the structures of the FK506 binding domain of Plasmodium vivax (PvFKBD) in unliganded form by NMR spectroscopy and in complex with FK506 by X-ray crystallography. We found out that PvFKBP35 exhibits a canonical FKBD fold and shares kinetic profiles similar to those of PfFKBP35, the homologous protein in P. falciparum, indicating that the parasite FKBP family members play similar biological roles in their life cycles. Despite the similarity, differences were observed in the ligand binding modes between PvFKBD and HsFKBP12, a human FKBP homolog, which could provide insightful information into designing selective antimalarial drug against the parasites.